2017
DOI: 10.1016/j.devcel.2017.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Ska Recruitment by Ndc80 Complexes to Kinetochores

Abstract: SUMMARY Yeast use the ring shaped Dam1 complex to slide down depolymerizing microtubules to move chromosomes, but current models suggest other eukaryotes do not have a sliding ring. We visualized Ndc80 and Ska complexes on microtubules by EM tomography to identify the structure of the human kinetochore-microtubule attachment. Ndc80 recruits the Ska complex so that the V-shape of the Ska dimer interacts along protofilaments. We identify a mutant of the Ndc80 tail that is deficient in Ska recruitment to kinetoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
6

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 54 publications
(125 reference statements)
2
59
6
Order By: Relevance
“…In addition, although the Ska1 MTBD is necessary and sufficient for Ska1 complex microtubule binding and spindle localization [2], we note that recent work has also suggested a contribution to microtubule interactions from Ska3 [28]. Ultimately, these activities must be regulated [13, 29, 30] and integrated with other players at the kinetochore, including the Ndc80 complex [2, 31, 32], to ensure faithful chromosome segregation during every cell division.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, although the Ska1 MTBD is necessary and sufficient for Ska1 complex microtubule binding and spindle localization [2], we note that recent work has also suggested a contribution to microtubule interactions from Ska3 [28]. Ultimately, these activities must be regulated [13, 29, 30] and integrated with other players at the kinetochore, including the Ndc80 complex [2, 31, 32], to ensure faithful chromosome segregation during every cell division.…”
Section: Resultsmentioning
confidence: 99%
“…Concomitantly, the Ska3 mutants deficient in Cdk1 phosphorylation failed to localize to kinetochores but retained their MT localization (Zhang et al, ). Contrary to these studies, fairly recently, an alternate mechanism for Ska recruitment to kinetochores was demonstrated via the N‐terminal unstructured tail of Ndc80 (Janczyk et al, ). Another study demonstrated that the direct interaction of the Ska complex (Ska1 subunit) with the MT plus‐end binding EB1 protein was responsible for the localization of Ska1 to the kMT interface (Thomas et al, ).…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, it is still unclear how the Ska and Ndc80 complexes interact with one another at the atomic level and how these two complexes are organized in three dimensions. In spite of these findings, Ska kinetochore recruitment seems more complicated because of two recent studies suggesting that the Ndc80 N‐terminus also plays a role in recruiting Ska to kinetochores . Janczyk et al .…”
Section: How Is Ska Targeted To Kinetochores?mentioning
confidence: 99%
“…Janczyk et al . isolated an Ndc80 tail mutant that retained a robust microtubule‐binding capacity, but was deficient in clustering along microtubule protofilaments . As a result, this mutant recruited less Ska to the kinetochore.…”
Section: How Is Ska Targeted To Kinetochores?mentioning
confidence: 99%